The Effect Of Education Level And Labor Absorption On Unemployment In Indonesia - Febri Rahmita; Purwaningsih, Selvi; Andriawan, Andriawan; Febriani, Ridha Fauzana; Winda; Izmuddin, Iiz (ADPEBI, 2022)
The problem of unemployment is a polemic for a country. The high population in Indonesia continues to grow, resulting in an increase in the number of existing workers. The current high number of workers exceeds the number of available jobs. The supply of labor that is more than the demand for labor will result in an increase in the number of unemployed. One of the factors associated with unemployment is alumni of a certain level of education, such as those from high schools and tertiary institutions, who are not absorbed in the labor market. High school graduates are faced with unequal competition with vocational high school graduates in terms of skills and work mentality. The availability of jobs to absorb high school graduates is still very small compared to vocational high school graduates. On the other hand, continuing education to college cannot guarantee success in getting a job as expected. This paper is expected to provide an overview and development of insights regarding the polemic of unemployment in Indonesia based on educational levels ranging from high school graduates to tertiary institutions. This research is a literature research with the object of study, namely literature and documents that examine the conditions of education and employment in Indonesia from the perspective of employment absorption, where the data collected is secondary data and then analyzed using descriptive analysis methods.